Philosophers past and present selected essays - Stroud, Barry (Oxford : Oxford University Press, 2011)
This volume of essays explores central ideas in the work of individual philosophers from Descartes, Berkeley, and Locke to Quine, Burge, McDowell, Goldman, Fogelin and Sosa. Stroud confronts a series of philosophical issues, and examines the sources, implications, and legacy of Hume's 'naturalism' and 'scepticism'.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Hume, David, -- 1711-1776 -- Influence; Philosophy -- History -- 20th century; Naturalism; Hume, David, -- 1711-1776.